2016
DOI: 10.1097/hcm.0000000000000125
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Study of the Change-of-Shift Report at the Patients’ Bedside

Abstract: Concerns about patient bedside change-of-shift reporting at a community hospital in northern Indiana stimulated the development of this qualitative phenomenological study. A review of the literature revealed a research deficit in acute care nurses' perceptions of bedside reporting in relation to compliance. The research question addressed in this study was, "What are acute care nurses' perceptions of the change-of-shift report at the patients' bedside?" Personal interviews were conducted on 7 medical, surgical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(44 citation statements)
references
References 11 publications
1
37
0
7
Order By: Relevance
“…Participants of this study reported that one way to minimize interruptions is to conduct BSR using a modified approach, where a portion of hand‐off occurs inside and outside the patient's room. This finding is further validated by a study conducted by Grimshaw et al (2016). Clinical nurses in their study reported that a modified approach should be used to decrease the time BSR takes and ensure all important, information, sometimes sensitive and difficult to discuss in front of the patient, is delivered.…”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…Participants of this study reported that one way to minimize interruptions is to conduct BSR using a modified approach, where a portion of hand‐off occurs inside and outside the patient's room. This finding is further validated by a study conducted by Grimshaw et al (2016). Clinical nurses in their study reported that a modified approach should be used to decrease the time BSR takes and ensure all important, information, sometimes sensitive and difficult to discuss in front of the patient, is delivered.…”
Section: Discussionsupporting
confidence: 80%
“…The findings of this study support the recommendation from AHRQ that some topics are not appropriate to discuss in the patient's presence. This finding is further validated by a qualitative study that found nurses were not able to say everything they wanted to at the bedside for fear of saying something that may upset the patient (Grimshaw et al., 2016). However, this study differed from AHRQ because it found that a modified approach was better, more feasible and made for a better hand‐off than a hand‐off of all critical content at the patient's bedside.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations